2017
DOI: 10.1002/aur.1741
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sex and age on prevalence rates of comorbid conditions in autism

Abstract: Individuals with ASD frequently experience one or more comorbid conditions. Here, we investigate the influence of sex and age-two important, yet understudied factors-on ten common comorbid conditions in ASD, using cross-sectional data from 4790 individuals with ASD and 1,842,575 individuals without ASD. Epilepsy, ADHD, and CNS/cranial anomalies showed exceptionally large proportions in both male (>19%) and female (>15%), children/adolescents with ASD. Notably, these prevalence rates decreased drastically with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 47 publications
5
62
1
3
Order By: Relevance
“…In line with other studies (Gurney et al 2006; Levy et al 2010; Lundstrom et al 2015; Nicholas et al 2009; Simonoff et al 2008; Supekar et al 2017; Wiggins et al 2015), we documented a high prevalence of co-occurring conditions/symptoms in those with ASD. As indicated by others (e.g., Levy et al 2010; Lundstrom et al 2015) and confirmed in our study, only a small proportion of children with ASD did not have any co-occurring condition/symptom.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In line with other studies (Gurney et al 2006; Levy et al 2010; Lundstrom et al 2015; Nicholas et al 2009; Simonoff et al 2008; Supekar et al 2017; Wiggins et al 2015), we documented a high prevalence of co-occurring conditions/symptoms in those with ASD. As indicated by others (e.g., Levy et al 2010; Lundstrom et al 2015) and confirmed in our study, only a small proportion of children with ASD did not have any co-occurring condition/symptom.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, affected individuals may have co-occurring conditions/symptoms. The most frequently reported are: intellectual disability (ID); Attention Deficit Hyperactivity Disorder (ADHD); developmental regression; behavioral, sleep, sensory processing, and gastrointestinal problems; and ASD-associated genetic conditions, such as Down syndrome, Fragile X syndrome (Bauman 2010; Gurney et al 2006; Kielinen et al 2004; Krakowiak et al 2008; Levy et al 2010; Lundstrom et al 2015; Simonoff et al 2008; Supekar et al 2017; Wiggins et al 2009). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies were carried out in Denmark [Abdallah et al, ; Maibing et al, ; Mouridsen, Rich, & Isager, ; Mouridsen, Rich, Isager, & Nedergaard, ], two studies in the United States [Joshi et al, ; Supekar, Iyer, & Menon, ], two in Sweden [Selten, Lundberg, Rai, & Magnusson, ; Stahlberg, Soderstrom, Rastam, & Gillberg, ], one in Norway [Bakken et al, ], one in Canada [Bradley et al, ], and one in the Netherlands [Fiksinski et al, ]. The sample sizes ranged from 12 [Bradley et al, ] to 9,062 [Selten et al, ] individuals with ASD and from 12 [Bradley et al, ] to 1,842,575 [Supekar et al, ] controls. Additionally, the mean ages of the samples ranged from 4.9 years old [Mouridsen, Rich, Isager, et al, ] to 32.2 ± 9.1 years old [Stahlberg et al, ].…”
Section: Resultsmentioning
confidence: 99%